Fusarium Species Associated with Corm Rot of Taro in Bogor - . WIDODO; . SUPRAMANA (Indonesian Society for microbiology, 2011)
In Bogor-West Java, corm rot disease of taro has devastated in many cropping areas and caused yield losses up to 70%. During preliminary studies, Fusarium species were constantly recovered when diseased materials, rotten corms and discolored petioles were incubated. The objectives of this study was to identify the Fusarium species associated with the corm rot disease in Bogor and determine their pathogenicity and hosts range. Samples were collected from 40 diseased corm samples taken in 9 sub-districts of Bogor. Two species, viz, Fusarium solani and F. oxysporum were identified based on the morphological characteristics. Among 40 Fusarium isolates recovered in this study, 70% were Fusarium solani and 30% were F. oxysporum. F. solani could infect to all tested edible Araceae , while F. oxysporum was only pathogenic to Colocasia esculenta. Both species of Fusarium did not cause any symptoms when inoculated on selected ornamental and legume crops. These results gave the indication that F. solani was probably pathogenic only to edible Araceae, but further inoculation assay on living taro plants are necessary to carry out in order to clarify this result.